Treatment of the subarachnoid-pleural fistula. Case report. - (:unkn) unknown (My University, 2000)
Subarachnoid-pleural fistula is a rare type of cerebrospinal fluid (CSF) fistula, and there are only several cases reported in the literature. The authors describe a 65-year-old male patient in whom a diagnosis of T7-8 disc herniation had been made. He underwent surgery via a right lateral extracavitary approach. Postoperatively he developed progressive respiratory distress and headache. A chest x-ray film revealed a pleural effusion, and computerized tomography (CT) myelography demonstrated a subarachnoidal-pleural fistula at the level at which the herniated disc had been removed. The patient had been managed via a CSF drainage system and a chest tube. He was discharged after relief of symptoms was attained. Subarachnoid-pleural fistulas can be secondary to traumatic injury and surgery, or they can be spontaneous. Patients present with rapidly filling pleural effusion and headache. A diagnosis can be established using CT myelography or myeloscintigraphy. Treatment is conservative, with the placement of a chest tube and insertion of a CSF drainage catheter, and surgical repair should be considered only if the conservative therapy fails.